Batch growth of wafer-scale nanocrystalline NbSe2 film for surface-enhanced Raman spectroscopy - Lin Huihui; Li Yiwen; Li Yuxin; Li Meng-Xuan; Wu Luyan; Chen Zhaolong; Li Jing (National Science Open)
Noble metal-based surface-enhanced Raman spectroscopy (SERS) has emerged as an ultrasensitive technique capable of detecting single molecules through their unique vibrational signatures. However, achieving robust SERS nanomaterials that combine significant enhancement factors, scalable reproducibility, and superior chemical stability remains a significant challenge. We present an oxygen-free vapor deposition technique for wafer-scale fabrication of nanocrystalline NbSe2 (NC-NbSe2) films on SiO2/Si substrates, which is compatible with batch production. The NC-NbSe2 films exhibit remarkable chemical stability across both crystalline domains (average size ~8.1 nm) and grain boundaries. This stability, combined with enhanced surface adsorption and a high density of states near the Fermi level, enables superior SERS performance. Rhodamine 6G detection demonstrates a sensitivity of 1×10−10 M, comparable to noble metal-based SERS substrates. Additionally, the NC-NbSe2 film maintains stable SERS signals under harsh thermal and chemical conditions. This scalable approach enables the creation of uniform, reproducible SERS atomic thin film, advancing applications in microelectronics and sensing technologies.